(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
In linguistics, semantics is the subfield that is devoted to the study of meaning, as inherent at the levels of words, phrases, sentences, and even larger units of discourse. Every word has a variety of senses and connotations which can be added, removed, or altered over time, often to the extent that cognates across space and time have very different meanings. The basic area of this study is to discuss how meaning of certain word borrowed from Arabic language is changing. Semantic change is a change in one of the meanings of a word. Therefore, the study confined itself to various types of semantic changes that affect Arabic loan words borrowed into Hausa language.